Semiotika Kepemimpinan Ganjar Pranowo: Strategi Indonesia-Sentris dalam Membangun Citra Nasional Melalui Politik Kuliner - Claudia Christianauli; J. A. Wempi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study originates from the shift in Ganjar Pranowo's communication style, which transitioned from a Java-centric focus to an Indonesia-centric approach, particularly in the lead-up to the announcement of the Indonesian presidential candidate. Ganjar strategically leveraged social media platforms, especially Instagram and TikTok, to disseminate engaging and interactive content. The research aims to analyze the transformation of Ganjar Pranowo's leadership style within the context of the preparations for the Indonesian presidential election. Employing a constructivist paradigm through a qualitative case study method, the research collected primary data via literature reviews and document analysis from Ganjar's social media posts and media coverage of his activities. The findings reveal that Ganjar's communication transformation, which utilized Indonesia-centric symbols and messages, successfully expanded his political appeal beyond his traditional base. Through a semiotic approach, it was uncovered that the consistent use of national symbols and narratives in his digital content has shaped a more inclusive public perception of his leadership image. This strategy not only strengthened Ganjar's image as a national leader but also fostered an emotional connection with a broader audience, ultimately bolstering public support in the lead-up to the presidential election.